Big trouble in Little China [videorecording (Blu-Ray)] - Richter, W. D. (Twentieth Century Fox Home Entertainment, 2009)
Jack Burton is a big-talking, wisecracking trucker who goes beneath the streets of San Francisco's Chinatown to battle an army of spirits when his friend's fiancee is kidnapped.